Metaphor as Sea Creature Naming Strategy in Akan - Wonkyi, Patrick Nana; Mireku-Gyimah, Patricia Beatrice; Dawson-Ahmoah, Grace Nana Aba (Linguistik Online, 2021)
The paper discusses the role of metaphor in the name construction of sea creatures among Akan (Mfantse) people within the purview of onomasiology. The role of metaphor in the naming of sea creatures has been understudied. This paper is a step towards filling the gap by analyzing the role metaphor plays in constructing naming units for sea creatures. This study has a qualitative research design. Twelve (12) fishers were purposely sampled, three (3) each from four fishing towns: Anomabo, Apam, Sekondi (Sekunde) and Moree (Mowure). The data collection tool was a semi-structured interview. The paper finds that likeness between sea creatures and static and/or dynamic entities triggers names for sea creatures. It concludes that, metaphor is employed to achieve simpler forms for salient features, communicate non-codable salient features and condense multiple features in the quest to name sea creatures among the Mfantse people. Through these vital roles, a general metaphor Sea Creatures are Land Animals/Entities is realized. The encyclopedic knowledge, which the Mfantse people have about their environment is realized through their naming strategies. It is recommended that the linguistics of naming percepts in indigenous Akan occupations be explored further.